Discovery of thiapyran-pyrimidine derivatives as potential EGFR inhibitors. Issue 19 (1st October 2020) - Xiao, Zhen; Chu, Cilong; Zhou, Lingjia; Zhou, Zhihui; Zhang, Qian; Yang, Feiyi; Yang, Zunhua; Zheng, Pengwu; Xu, Shan; Zhu, Wufu
Graphical abstract: A series of thiapyran-pyrimidine derivatives were synthesized, and the most promising compound 13a showing IC50 of 0.13 µM against EGFR T790M/L858R kinase was proved to be a potential EGFR inhibitor. Highlights: A series of novel thiapyran-pyrimidine derivatives (10a–10h, 11a–11g, 12a–12f, 13a–13f, 14a–14f ) were designed and synthesized. Most compounds showed excellent antiproliferative activity against cancer cell lines. Further experiments indicated that 13a could block A549 cells in G2/M phase and induce H1975 cells apoptosis. The results prompted that compound 13a may be a potential selective EGFR inhibitor. Abstract: A series of novel thiapyran-pyrimidine derivatives (10a–10h, 11a–11g, 12a–12f, 13a–13f, 14a–14f ) were synthesized and their antiproliferative activities were tested. Most of the target compounds showed good activity on one or more cancer cell lines but low activity on human normal cell LO2. The most promising compound 13a exhibited the similar IC50 values on A549 and H1975 cell lines to the lead drug Olmutinib, and exhibited excellent activity and selectivity on EGFR T790M/L858R in the kinase experiment. AO and Hoechst33258 staining indicated that 13a could effectively induce H1975 cells apoptosis. Cell cycle and apoptosis analysis suggested that 13a could block cancer cells in G2/M phase and induce into late apoptosis in a manner of concentration-dependent. The structure–activity relationship of 13a was analyzed to explore its mechanism. All the results showed that 13a was a promising EGFR inhibitor.